Comparative study of ovule and fruit development in species of Hypolytrum and Rhynchospora (Cyperaceae, Poales) - Coan, A. I. [UNESP]; Alves, M. V.; Scatena, V. L. [UNESP] (Springer Wien, 2008)
The development of the ovule and of the fruit of Hypolytrum bullatum and H. schraderianum (Mapanioideae) and of Rhynchospora consanguinea and R. rugosa (Cyperoideae) are described. All species share anatropous, bitegmic and crassinucellate ovules, funicular obturator, megagametophyte of the Polygonum type, presence of starch grains in the mature megagametophyte, free-nuclear endosperm, Onagrad-type embryogeny, testal-tegmic seed, and a simple fruit of the achene type. Rhynchospora species have characters typical of the family: micropyle formed by the inner integument alone; 3-4-layered parietal tissue; and hard achene. Hypolytrum species differ in those characters by presenting a slightly zigzag micropyle formed by both integuments connected with the funicular obturator, 5-8-layered parietal tissue, and fibrous-spongy achene. The peculiar formation of the micropyle in Hypolytrum is a feature reported here for the first time in the family. The ontogeny provides evidence for a better understanding of the dispersal unit in Hypolytrum supporting the classification as a true achene, like that of Rhynchospora, which is characteristic of the family.
Keywords: micropyle; funicular obturator; megagametogenesis; achene; Hypolytrum bullatum; Hypolytrum schraderianum; Rhynchospora consanguinea; Rhynchospora rugosa